Decision-making and global environment in the international market expansion strategy of the firm and implications to international performance - Myllymäki, Linda (My University, 2022)
The research on international market expansion strategy has previously mainly focused on examining the differences between two opposing strategies: market concentration and mar-ket diversification. Hence, we still know little how decision-making logics of causation and effectuation logics affect the selection of international market expansion strategy of micro firms and SMEs. Therefore, a study focusing on application of decision-making logic and glob-alization drivers in the external environment while expanding to international markets and choosing the international market expansion strategy is novel. Thus, the aim of this study is to examine the effect of causation and effectuation in addition to the globalization drivers in the external environment on international market concentration and diversification strategy, and finally, the effect of the international market expansion strategy on firm performance. Furthermore, the selected methodological tools for this thesis allow the examination of the relationships between variables which has not previously been done within effectuation studies. The data for this thesis was collected through an online survey in Webropol as a part of a larger research project that focuses on growth and decision-making of international Finnish based firms. The research project was organized as a collaboration between University of Vaasa, University of Eastern Finland and a Finnish government organization for innovation funding and trade agency called Business Finland. The sample consisted of 382 Finnish based micro firms and SMEs with international sales, and a total of 208 valid responses were re-ceived resulting in response rate of 57,46%. The data was analyzed using the SPSS applica-tion. The findings of this study indicate that firms using effectual reasoning when making decisions will more likely to follow international market diversification strategy. Furthermore, when there are stronger globalization drivers in the firm’s external environment it is more viable to adopt international market diversification strategy. The results also suggest that by following international market diversification strategy the firm will reach higher performance levels than when following a market concentration strategy. However, the results show that re-gardless of the chosen international market expansion strategy performance of the firm will increase when expanding to new international markets.

Tutkimus kansainvälisestä markkinastrategiasta on aikaisemmin keskittynyt pääsääntöisesti vertailemaan kahta eri markkinastrategiaa, keskittämis- ja hajauttamisstrategiaa. Emme kuitenkaan vielä tiedä miten päätöksentekologiikka, kausaatio ja effektuaatio-logiikka, vaikuttaa mikro- ja pienten ja keskisuurten (PK) yritysten markkinastrategian valintaan. Tutkimus, joka keskittyy kansainvälisen päätöksentekologiikan ja yrityksen ulkoisen ympäristön globalisaatiotekijöiden vaikutukseen yrityksen laajentuessa uusille kansainvälisille markkinoille ja markkinastrategian valintaan on uutta. Tämän tutkimuksen tarkoituksena on selvittää kausaatio- ja effektuaatio-logiikan ja ulkoisen ympäristön globalisaatiotekijöiden vaikutusta keskittämis- ja hajauttamisstrategiassa, sekä markkinastrategian vaikutusta kansainväliseen suorituskykyyn. Lisäksi, tähän tutkimukseen valitut metodologiset menetelmät sallivat muuttujien välisten suhteiden keskinäisen vertailun jota ei ole aikaisemmin hyödynnetty effektuaatio-tutkimuksessa. Tutkimus toteutettiin kvantitatiivisena tutkimuksena internetkyselyllä Webropol-järjestelmässä. Tämä tutkimus oli osa laajempaa tutkimusprojektia, joka tutkii suomalaisten kansainvälisten yritysten kasvua ja päätöksentekoa. Tutkimusprojekti järjestettiin yhteistyössä Vaasan yliopiston, Itä-Suomen yliopiston sekä Business Finlandin kanssa. Tutkimusotos koostui 382 suomalaisesta mikro- ja PK-yrityksestä, joilla oli kansainvälistä myyntiä. Vastauksia saatiin 208 kappaletta vastausprosentin ollessa 57,46%. Data analysoitiin SPSS-järjestelmällä. Tutkimustulokset osoittavat, että yritykset, jotka hyödyntävät päätöksenteossaan effektuaatio-logiikkaa valitsevat todennäköisemmin kansainvälisen hajauttamisstrategian. Lisäksi, kun yrityksen ulkoisessa ympäristössä on voimakkaita globalisaatiotekijöitä, yrityksen on kannattavampaa valita kansainvälinen hajauttamisstrategia. Tutkimustulosten mukaan yritykset, jotka seuraavat kansainvälistä hajauttamisstrategiaa yltävät parempaan suorituskykyyn, kuin yritykset, jotka ovat valinneet kansainvälisen keskittämisstrategian. Tutkimustulokset osoittavat kuitenkin, että riippumatta valitusta markkinastrategiasta, kansainvälinen suorituskyky parantuu yrityksen laajentuessa uusille markkinoille.
Keywords: kansainvälistyminen; strategiat; markkinointi; kansainvälisyys; pienet ja keskisuuret yritykset; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business